Estudio para determinar la producción de pastos en el rendimiento de leche en Buenos Aires, cantón Urcuqui, provincia de Imbabura - Lomas Revelo, Justo Javier (2018)
SUMMARY This study aims to promote alternative solutions to the problem of lack of rotation and forage mixtures, in the area for the increase in milk production in the community of the Buenos Aires Mercy. Since the importance of pasture production for livestock feed is one of the important points in the area, we want to investigate this practical work of pasture management and its impact on dairy production. For the development of this project, different research methods and techniques are applied, using descriptive statistics, where the collection of information is analyzed and characterized, with the aim of seeking alternative solutions to the issues already raised about the problems that affect the pasture cultivation and milk production, in addition, the main shortcomings in milk production were determined, references are made to improve dairy yield and increase their economic income to producers, the pasture cultivation that takes place daily in the different places. According to the results achieved, it can be known that 100% of the people of the community have pasture crops, which are used for livestock feed in milk production, the most representative grass in the area is the Kikuyo with which they have 70% of the participants of the survey followed by honey and common pasture with 20 and 10%, pastures that are dedicated exclusively to livestock feed, What the participants mention is that the nutritional requirements of the animals in the area are high for what they need yielding pastures, to improve the dairy and economic yields of the area, 80%, of the participants of the community, does not perform fertilization, while 20% if made of each grazing.